Cross section deformation of heterogeneous rectangular welded tube in rotary draw bending considering different yield criteria. (January 2021) - Liu, Hailong; Liu, Yuli
Abstract: Heterogeneous rectangular welded tube has serious anisotropy of parent metal and weld zone, in order to improve the prediction accuracy of cross-section deformation of tube in rotary draw bending (RDB), it is necessary to select the appropriate yield criterion to describe the anisotropic characteristics of heterogeneous rectangular welded tube. So the anisotropic parameters of Hill'48 and Barlat'89 yield criteria of parent and weld zone were obtained by using the digital image correlation test, then FE models of RDB of rectangular welded tube using different yield criteria were established. Based on these established FE models, the cross section deformation of thin-walled heterogeneous rectangular welded tube in RDB considering different yield criteria was researched. The results showed that, for the height and width deformation ratio of rectangular welded tube, the simulated results obtained by Mises, Barlat'89 and Hill'48 yield criteria in sequence, gradually increased to experimental results, this indicated that Hill'48 can well describe the anisotropic characteristic of rectangular welded tube. Further, under the condition of different bending angles and different core numbers, the maximum height deformation ratio obtained by Mises, Barlat'89 and Hill'48, successively, gradually increased to experimental results, which meant that Hill'48 anisotropic yield criterion was the most suitable one to predict cross section deformation of QSTE700 rectangular welded tube in RDB.